LIMITATION THEORY DAN PENERAPANNYA PADA AYAT AL-QURAN: Studi Hermeneutika Muhammad Syahrur - Suryana Alfathah (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2023)
This paper purposes to discuss how the hermeneutical model offered by Muhammad Syahrur in understanding the Koran, namely the theory of hudud and examples of its application in responding to problems in society. This research is included in the type of qualitative research using literature study methods. The method used in the analysis is a descriptive method of analysis through Muhammad Syahrur's limitation theory approach. The result of this study is that Syahrur's Hermeneutics, in this case is the hudūd theory, which is a completely new and original concept in the study of interpretation. Boundary theory introduces a construction in understanding the verses of muhkamat (law) where it states that in the process, there are two main dimensional movements in Islamic teachings, namely istiqamah and hanifiyyah. Istiqamah (constant movement) is a rule that has been established by Allah SWT and hanfiyyah is a change from time and place that is always dynamic. So that the ijtihad space is carried out as the hanifiyyah progresses but remains under the decree (hudud) of Allah SWT. An example of applying this concept is when understanding the verses about the headscarf and female genitalia. Based on Syahrur's observations, the minimum limits for a woman's private parts are al juyub (breasts, genitals, under the armpits and buttocks) while the maximum limits are the entire body except the face and palms. However, Syahrur's understanding certainly has quite risky consequences when applied to the present. Even though he received a lot of criticism, Syahrur's idea certainly became a breakthrough in Islamic thought which has a desire to be the answer to problems in society.